Disruption of TCBA1 associated with a de novo t(1;6)(q32.2;q22.3) presenting in a child with developmental delay and recurrent infections. Issue 2 (20th May 2005) - Yue, Y; Stout, K; Grossmann, B; Zechner, U; Brinckmann, A; White, C; Pilz, D T; Haaf, T
Abstract : A boy with developmental delay, particularly of speech, a distinct face, antineutrophil cytoplasmic antibodies, and recurrent infections was found to have an apparently balanced de novo t(1;6)(q32.3;q22.3) translocation. Fluorescent in situ hybridisation with BAC/PAC clones and long range polymerase chain reaction products assessed in the human genome sequence localised the chromosome 1 breakpoint to a 9.8 kb segment within a hypothetical gene, LOC388735, and the chromosome 6 breakpoint to a 12.8 kb segment in intron 4 of the T-cell lymphoma breakpoint-associated target 1 ( TCBA1 ) gene. Disruption and/or formation of TCBA1 fusion genes in T cell lymphoma and leukaemia cell lines suggests a role for this gene in tumorigenesis. The isolated mouse Tcba1 gene shows 91% amino acid sequence similarity with human TCBA1 . It is expressed in fetal and adult brain and with lower levels in liver and testis. The human gene has been reported to be expressed exclusively in brain and thymus. Reduced TCBA1 expression in brain and thymus may explain at least some of the symptoms in this patient. It is concluded that germline alterations of the TCBA1 gene are associated with developmental delay and typical physical features.